Neuraxial Analgesia Effects on Labor Progression: Facts, Fallacies, Uncertainties, and the Future. Issue 4 (December 2015) - Grant, E.N.; Tao, W.; Craig, M.; McIntire, D.; Leveno, K.
Abstract : ( BJOG . 2015;122(3):288–293)